2016
DOI: 10.1093/ageing/afw151
|View full text |Cite
|
Sign up to set email alerts
|

Let's all get home safely: a commentary on NICE and SCIE guidelines (NG27) transition between inpatient hospital settings and community or care home settings

Abstract: Safe and appropriate transition between inpatient settings and the community is one of the major challenges facing the modern NHS. The National Institute for Health and Care Excellence in conjunction with the Social Care Institute for Excellence published guidance on this challenging area in December 2015. This commentary provides context, summary and discussion of the key areas covered. The guidance particularly emphasises the importance of a person-centred approach in which patients are individuals and equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…First, our study revealed that the current process of information transfer is suboptimal. Information lacking in the care transition process identified in previous studies includes prior investigations, 23 medication, 24 and adequate attention to assessing comprehensive social conditions, especially among the elderly 25 . Our participants identified similar items, and all agreed that improving information transfer may improve the current care transition process.…”
Section: Discussionmentioning
confidence: 63%
“…First, our study revealed that the current process of information transfer is suboptimal. Information lacking in the care transition process identified in previous studies includes prior investigations, 23 medication, 24 and adequate attention to assessing comprehensive social conditions, especially among the elderly 25 . Our participants identified similar items, and all agreed that improving information transfer may improve the current care transition process.…”
Section: Discussionmentioning
confidence: 63%
“…Some parallels with other broad-based initiatives such as intermediate care can be seen. In the UK where intermediate care concepts have been operationalised, they include four types of intervention: crisis response, home-based care, bed-based care and reablement 32. The category of home-based care in this review corresponds with the hospital at home category.…”
Section: Discussionmentioning
confidence: 99%
“…This was an important omission which might have been averted through more robust application of the avoidable displacement from home framework. Likewise, including place-based care as an analytical theme would have revealed degrees of service integration and fragmentation, especially for interventions that seek to integrate external care with services at home 32. It was not possible to determine the degree of service integration for most interventions, but the available evidence for the medication review intervention indicated that it did not fully satisfy Kodner and Kyriacou’s definition of integrated care 7.…”
Section: Discussionmentioning
confidence: 99%
“…First, our study revealed that the current process of information transfer is suboptimal. Information lacking in the care transition process identi ed in previous studies include prior investigations 23 , medication 24 , and adequate attention to assessing comprehensive social conditions, especially among the elderly 25 . Our participants identi ed similar items, and all agreed that improving information transfer may improve the current care transition process.…”
Section: Format Of the Referral Lettermentioning
confidence: 99%